Geotourism and Rural Development, Baktiraja Subsub-District : Case Study Toba Caldera Area Humbang Hasundutan Regency - Muzambiq, Said (Media Wisata, 2023)
This research aims to evaluate the achievement of rural development in the study area after UNESCO designated Toba Caldera Geopark as a member of the Global Geopark Network (GGN) in July 2020. For that purpose, the authors conduct research to measure the relationship of geotourism with rural development in the area. The methods employed are library research, discussion, observation, field trips and questionnaires to 127 respondents from the village government officers, students, MSME communities and Youth Organizations. The results show that average: 65% of all respondents understand the existence of geotourism and geosites in their area, although only around 40% know precisely two out of 16 existing geosites in the area. There are 60% of them feel improvement in their economy with the presence of this geotourism. After the designation of this area as a Tourism Village Pilot Project in September 2018, more than 2/3 of the MSMEs businessmen feel an increase in consumer visits and receive an increase in revenue of up to 70%. However, questionnaires related to the improvement after the designation of Toba Caldera as UNESCO GGN are unable to be reconciled by them since the Covid19 pandemic also impacts them